Resonant Raman scattering of ZnSxSe1−x solid solutions: the role of S and Se electronic states. Issue 11 (17th September 2015) - Dimitrievska, M.; Xie, H.; Jackson, A. J.; Fontané, X.; Espíndola-Rodríguez, M.; Saucedo, E.; Pérez-Rodríguez, A.; Walsh, A.; Izquierdo-Roca, V.
Abstract : A combined theoretical and experimental study of the enhancement in the Raman mode intensities of ZnSSe compounds, under various resonant conditions, is presented, leading to more detailed insights into the role of chalcogen electronic states in the photon–matter interaction. Abstract : A comprehensive Raman resonance scattering study of ZnS x Se1− x (ZnSSe) solid solutions over the whole compositional range (0 ≤ x ≤ 1) has been carried out using 325 and 455 nm excitation wavelengths. The Raman scattering intensities of LO ZnS-like and ZnSe-like phonon modes, corresponding to pure S and Se vibrations, respectively, are revealed to be significantly enhanced when excited with 325 nm excitation in the case of S vibrations, and with 455 nm in the case of Se vibrations. This behavior is explained by the interaction of the excitation photons with the corresponding S or Se electronic states in the conduction band, and further confirmed by first principles simulations. These findings advance the fundamental understanding of the coupling between the electronic transitions and photons in the case of Raman resonance effects, and provide inputs for further studies of lattice dynamics, especially in the case of chalcogenide materials. Additionally, the coexistence of modes corresponding to only S vibrations and only Se vibrations in the ZnSSe alloys makes these results applicable for the compositional assessment of ZnSSe compounds.